2020
DOI: 10.21037/qims.2019.12.06
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics prediction model for the improved diagnosis of clinically significant prostate cancer on biparametric MRI

Abstract: Background: To evaluate the potential of clinical-based model, a biparametric MRI-based radiomics model and a clinical-radiomics combined model for predicting clinically significant prostate cancer (PCa).Methods: In total, 381 patients with clinically suspicious PCa were included in this retrospective study; of those, 199 patients did not have PCa upon biopsy, while 182 patients had PCa. All patients underwent 3.0-T MRI examinations with the same acquisition parameters, and clinical risk factors associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 39 publications
1
47
0
Order By: Relevance
“…In a study by Li et al., patients with benign lesions and GS = 6 were grouped into clinically insignificant PCa. After univariate and multivariate logistic analysis, the results showed that age, tPSA, fPSA and clinical factors were important factors for predicting significantly important PCa, with an AUC value of 0.842 ( 24 ). Our study also showed that age and PSAD were important predictors of PCa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Li et al., patients with benign lesions and GS = 6 were grouped into clinically insignificant PCa. After univariate and multivariate logistic analysis, the results showed that age, tPSA, fPSA and clinical factors were important factors for predicting significantly important PCa, with an AUC value of 0.842 ( 24 ). Our study also showed that age and PSAD were important predictors of PCa.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have confirmed that BPH is often characterized by the increased number of cells of different components, not only in the number of gland cells, but also in the number of smooth muscle cells, or may even consist entirely of stromal nodules ( 31 ). However, the pathological changes of PCa are mostly because of the increase of the number of cancer cells and the changes of extracellular space ( 24 ). Therefore, we speculated that the heterogeneity of cellular components may be the reason for the lower consistency of ultrasound radiomics in benign prostatic lesions than in PCa.…”
Section: Discussionmentioning
confidence: 99%
“…At least three mpMRI sequences are needed to diagnose PCa: T2-weighted imaging (T2WI), dynamic contrast-enhanced imaging (DCEI), and diffusion-weighted imaging (DWI). In the second edition of the Prostate Imaging Reporting and Data System (PI-RADS), DCEI plays a minor role, but DWI and its derived apparent diffusion coefficient (ADC) maps have become the main diagnostic parameters (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Radiomics (1)(2)(3)(4)(5) holds great promises in clinical oncology to aid better diagnosis, prognosis, and personalized clinical decision making, as witnessed by a huge number of research studies published in recent years (6)(7)(8)(9)(10)(11)(12)(13). However, the broad validity and generality of radiomics are much hindered by the concerns on its reliability (14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%